2016
DOI: 10.1016/j.jtusci.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS/MS characterization of the forced degradation products of ezetemibe: Development and validation of a stability-indicating UPLC method

Abstract: The present study reports the characterization of four degradation products from ezetemibe (EZB) through liquid chromatography-tandem mass spectrometry (LC-MS/MS) and the development of a validated and stability-indicating reversedphase ultra-performance liquid chromatographic method for the determination of EZB in the presence of its process-related impurities in bulk drugs. The forced decomposition of EZB was carried out and studied under acidic, basic, oxidative, photolytic and thermal conditions. The degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…Peak purity for the peaks acquired from various degradation tests was observed utilizing tools from the empower programme, and it was declared that the FEL peak was pure and homogenous from all examined stress samples. Mass balance values were determined from the stressed samples, and it was found that all of the results are greater than 99.6% (Table 3), which is consistent with the findings of earlier studies [24]. Thus, it was determined that the devised technique was stable and specific to Imp 1 and its degradation products.…”
Section: Dp1 (M/z: 356)supporting
confidence: 86%
See 1 more Smart Citation
“…Peak purity for the peaks acquired from various degradation tests was observed utilizing tools from the empower programme, and it was declared that the FEL peak was pure and homogenous from all examined stress samples. Mass balance values were determined from the stressed samples, and it was found that all of the results are greater than 99.6% (Table 3), which is consistent with the findings of earlier studies [24]. Thus, it was determined that the devised technique was stable and specific to Imp 1 and its degradation products.…”
Section: Dp1 (M/z: 356)supporting
confidence: 86%
“…The two molecular ions fragments formed under the base stress condition which are as follows: 1. [24].…”
Section: Dp1 (M/z: 356)mentioning
confidence: 99%
“…The chemical degradation assays on HO-AAVPA were followed using HPLC (Fig. 2 ) to separate the generate by-products to be analyzed (molecular weight) by LC–MS/MS as was for ezetemibe 39 . Once the HO-AAVPA was subjected to force degradation studies (acid and alkaline conditions, oxidation, heat, sunlight, the oxidation), only the sunlight generates a by-product that correspond to dimmer HO-AAVPA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same thing shows that the MCP was affected by acidic medium to a certain level. It is an indication for both bulk drug and generic product manufacturers to optimize the critical quality aspects to evade the exposure of HCl during the manufacturing pro- cess (Kancherla et al, 2016;Babu et al, 2018).…”
Section: Rp-hplc Methods Development For the Stabilityindicating Technmentioning
confidence: 99%